Oral Presentations Abstracts: THE COMPARATIVE EFFECTIVENESS OF SYNCHRONOUS AND ASYNCHRONOUS ONLINE BIOETHICS LECTURE DELIVERY ON STUDENT LEARNING IN DISCUSSION BOARD POSTS - CLARK SCHIFF, Jenny; GREER, Michael L. J.; FELDER, Ryan; KOLAK, Julia; SMOLENSKI, Joanna; FERGUSON, Kyle; CUMMINS, Paul; RHODES, Rosamond (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Due to the COVID-19 pandemic, many courses that were once in person are now online. In our new “physically distanced” world, bioethics faculty has had to adapt quickly. To bridge the gap created by eliminating face-to-face interaction for two cohorts of international bioethics students, we combined them and created five four-week online bioethics mini-courses: “Justice and Pandemic Diseases,” “Reproduction,” “Pediatrics,” “Organ Transplantation,” and “Death and Dying.” Each mini-course involved required readings, weekly lectures, discussion board participation, and a final paper. Our study evaluates the comparative effectiveness of synchronous and asynchronous lecture delivery on student learning as evidenced in online discussion board posts in the mini-courses. Students from both cohorts received the same educational materials but were divided into two groups for alternating synchronous and asynchronous Zoom lectures. We developed a standardized rubric, and raters have been using it to score each student’s initial posts. We hypothesized that, for the same discussion board question, students’ scores on posts following synchronous lectures will on average be higher than those following asynchronous lectures. We will finalize our data analysis at the conclusion of the final mini-course in late March and learn if the data support our hypothesis. There are many challenges in determining the comparative effectiveness of synchronous and asynchronous teaching on overall student learning. Our study addresses a modest yet worthwhile question, whether and to what degree these different lecture modalities impact student learning evidenced in discussion board posts. Our findings will contribute to bioethics pedagogical research during these challenging times.